Secondary Metabolite Profiling, In-Silico, and In Vitro Study of Acriopsis liliifolia Roots as Active Cosmetic Ingredients - Wannawijaya, Nashwa Maheswari; Khoeriyah, Ni’matul; Apsari, Cintya Nurul; Nuraini, Latifa (Bogor Agricultural University, Indonesia, 2025)
Beauty and health are currently topics of the global trend. Secondary metabolites from natural sources have become increasingly important for their potential application in cosmetics. This study aims to investigate the potential of Acriopsis liliifolia roots (ALR) as a source of active cosmetic ingredients through secondary metabolite profiling, in silico, and in vitro analysis. A. liliifolia, a medicinally valuable orchid species, was selected due to its rich phytochemical content, which could offer beneficial properties for skin, such as skin-brightening effects. The roots of A. liliifolia were subjected to microchemical assay and metabolite profiling using Liquid Chromatography High-Resolution Mass Spectrometry (LC-HRMS) to determine the bioactive compounds. Additionally, the identified compounds were evaluated through molecular docking studies to assess their interactions with key skin-related enzymes, such as tyrosinase. In vitro studies were conducted to confirm the activity of secondary metabolites of A. liliifolia root on the inhibition of tyrosinase. Microchemical results showed that ALR is positive for phenolics and alkaloids. Metabolite profiling revealed the presence of 125 compounds, then 14 of the most potential compounds were selected. The docking studies exhibit that 1,3-dilinolenoylglycerol had the lowest S-score of -9.54 kJ/mol and lower than kojic acid, suggesting that 1,3-dilinolenoylglycerol has the potential to inhibit tyrosinase. The in vitro studies showed that A. liliifolia roots extract at 250 mg/ml can inhibit tyrosinase (150 U/ml) by 42.56%. However, further research is required to ascertain its potential effect and safety assessment of cosmetics.